The Role of 5G Technology in Improving the Speed and Quality of Internet Services in Urban Areas - Nurhuda; Rida Ramli; Firta Dewi (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
This study examines the performance of 5G technology in dense urban areas, where population growth and digital activities such as video streaming and IoT are putting pressure on 4G network capacity. The study aimed to evaluate the role of 5G in improving download speeds, latency, and stability of internet services through empirical comparisons with 4G. This quantitative descriptive study used a population of internet users around the University of West Sulawesi with a purposive sample of 50 respondents aged 18-45 years. Instruments included the Ookla Speedtest application and a Likert scale questionnaire, analyzed with descriptive statistics and t-tests using SPSS 26. The results showed 5G download speeds of 300-600 Mbps, upload speeds of 50-120 Mbps, latency of 8-12 ms, and very high stability, with streaming quality improvements of up to 90%. The conclusion states that 5G significantly supports smart city transformation despite being limited to a local sample